Diagnostic importance of cystatin C and creatinine for contrast-induced acute kidney injury - Pilčević, Dejan; Rančić, Nemanja; Jović, Zoran; Rabrenović, Violeta; Antić, Svetlana; Petrović, Marijana; Petrović, Dejan; Maksić, Djoko (Vojnosanitetski pregled, 2021)
Background/Aim. Contrast-induced acute kidney injury (CI-AKI) is a common complication after the percutaneous coronary intervention, associated with a prolonged hospital stay, increased medical costs, and risk of adverse clinical outcomes. The aim of this study was to compare changes in levels of serum creatinine (sCr) and cystatin C (sCyC) 24 h after coronary angiography as an early indicator of CI-AKI. Methods. The study included 45 patients with chronic renal failure grade I–III scheduled for coronary angiography. Levels of sCr and sCyC were measured a day before and 24 h after coronary angiography. CI-AKI was defined as a 25% and 10% increase of sCr and sCyC levels from baseline within 24 h from contrast media exposure, in the absence of alternative causes. Results. Mean sCr and sCyC concentrations were 86.4 ± 22.6 µmol/L and 1.18 ± 0.52 mg/dL, respectively before contrast administration, and 90.6 ± 24.1 µmol/L and 1.24 ± 0.65 mg/dL, respectively 24 h after contrast media exposure. sCr-based CI-AKI occurred in 4 patients (8.89%) and sCyC-based CI-AKI was detected in 19 patients (42.22%) after the contrast procedure (p < 0.001). Conclusion. sCyC level measured 24 h after contrast media exposure is a more sensitive indicator of CI-AKI than sCR level.
Keywords: kidney failure, acute; kidney failure, chronic; coronary angiography; creatinine; cystatin c